Parental Knowledge on car Safety for Children: An Israeli Survey - Michal Hemmo-Lotem; Jacob Urkin; Liri Endy-Findling; Joav Merrick (The Scientific World Journal)
The objective of this study was to assess the level of parental car safety knowledge and actual behavior regarding their children under the age of 15 years. This study forms part of the National Center for Child Safety and Health in Israel (Beterem) program to examine awareness on child safety. Seven hundred and five Jewish families with at least one child at home younger than 15 years (a total of 1,345 children) were used as a randomized sample of the Jewish population. A telephone survey was conducted by professional interviewers using a questionnaire developed by injury prevention specialists consisting of seven knowledge questions and a diagram that described the usual seating positions and restraining method of the family members in the family car. Concerning knowledge about injury prevention, the rate of incorrect answers was high,64% in regard to the proper car seats for age and 84% in regard to the age for booster seats. Sixty five per cent of parents did not know what a booster seat was and 54% did not know that the proper place for children was in the back seat. The average of incorrect answers was 4.86 out of 7 (SD=1.45) correlated with low socioeconomic status. Concerning care safety behavior 60% per cent of babies and 38% of toddlers were not restrained properly. This study should alert planners and policy makers to the need of implementation of educational prevention programs for the Israeli public of parents concerning car safety for children in order to reduce childhood injury.